Preferences for sexual health smartphone app features among gay and bisexual men - Ventuneac, Ana (AIDS Behav, 2018)
Given the popularity of Geosocial networking applications (“apps”) among gay, bisexual, and other men who have sex with men (GBMSM), this study sought to examine GBMSM’s willingness to use sexual health and behavior tracking features if integrated within apps they are already using to meet sexual partners. Most GBMSM (91%) recruited on a popular app reported interest in one or more sexual health app features, including features to find LGBT-friendly providers (83%), receive lab results (68%), schedule appointment reminders (67%), chat with a healthcare provider (59%), and receive medication reminder alerts (42%). Fewer GBMSM were interested in tracking and receiving feedback on their sexual behavior (35%) and substance use (24%). Our data suggest that integrating sexual health and behavior tracking features for GBMSM who use apps could be promising in engaging them in HIV prevention interventions. Further research is needed on GBMSM’s perspectives about potential barriers in using such features.